Pre- and post-procedural quality indicators for colonoscopy: A nationwide survey. Issue 7 (July 2016) - Paggi, Silvia; Amato, Arnaldo; Anderloni, Andrea; Annese, Vito; Barresi, Luca; Buda, Andrea; Cesaro, Paola; Di Giulio, Emilio; Gullotti, Giuseppe; Fabbri, Carlo; Fiori, Giancarla; Fuccio, Lorenzo; et al.
Abstract: Background: The provision of high-quality colonoscopy can be assessed by evaluating technical aspects of the procedure and, at individual center level, by comparing structural indicators and institutional policies for managing peri-procedural issues with guideline recommendations. Aim: To assess the colonoscopy quality (CQ) in Italy at center level. Methods: Gastroenterologists participating in a nationwide colonoscopy education initiative provided information on structural indicators of their centers and on institutional policies by answering 10 multiple-choice clinical scenarios. Practice variation across centers and compliance with guidelines were analyzed. Results: Data from 282 Italian centers were evaluated. Overall, a significant proportion of centers did not meet CQ standards as concerns endoscopy facilities and equipments (e.g., dedicated recovery room, dirty-to-clean path, reporting software). CQ assurance programs were implemented in only 25% of centers. Concerning peri-procedural issues, main discrepancies with guidelines were recorded in the underuse of split-dose preparation (routinely adopted by 18% of centers), the routine request of coagulation tests prior to colonoscopy (30%), the routine interruption of aspirin for polypectomy (18%), and the adoption of 3-year surveillance for low-risk adenoma (49%). Conclusions: Present survey shows a significant variation in the CQ of endoscopy centers in Italy on many items of colonoscopy practice that should be targeted for future interventions.